2008
DOI: 10.1097/brs.0b013e3181715304
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Single Nucleotide Polymorphism in the Insulin-Like Growth Factor-1 Receptor Gene With Spinal Disc Degeneration in Postmenopausal Japanese Women

Abstract: We suggest that a genetic variation at the IGF1R gene locus is associated with spinal disc degeneration, in line with the involvement of the IGF1R gene in the cartilage metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 45 publications
(32 reference statements)
1
28
0
Order By: Relevance
“…Attempting to elucidate the pathogenesis of lower back pain, we previously investigated the association of various genetic factors with spinal degeneration [23][24][25][26]. In our previous studies on the common genetic variants associated with spinal degeneration, we found that polymorphism of the LRP5 gene correlated with osteophyte formation [26], while that of the IGF1R correlated with disc space narrowing [25]. Here, we demonstrated that Japanese postmenopausal women with two T alleles at intron 2 of the HAPLN1 gene had significantly higher scores for both osteophyte formation and disc space narrowing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Attempting to elucidate the pathogenesis of lower back pain, we previously investigated the association of various genetic factors with spinal degeneration [23][24][25][26]. In our previous studies on the common genetic variants associated with spinal degeneration, we found that polymorphism of the LRP5 gene correlated with osteophyte formation [26], while that of the IGF1R correlated with disc space narrowing [25]. Here, we demonstrated that Japanese postmenopausal women with two T alleles at intron 2 of the HAPLN1 gene had significantly higher scores for both osteophyte formation and disc space narrowing.…”
Section: Discussionmentioning
confidence: 99%
“…Both lateral projections in the lateral decubitus position and A-P projections in the supine position were obtained at a constant focus-film distance of 1.5 m. The severity of spinal degeneration, including osteophyte formation, endplate sclerosis, and disc space narrowing, was semiquantitatively assessed from the T4/5 to L4/5 disc level or from the T4 to L4 level using the grading scale described by Genant [31]. Next, we radiographically assessed spinal disc degeneration by using a previously reported scoring system [23][24][25][26]. In brief, osteophyte formation at a particular disc level was graded 0-3 degrees; endplate sclerosis, 0-2 degrees; disc space narrowing, 0-1 degree.…”
Section: Radiographic Grading Of Spinal Disc Degenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between the A1330V polymorphism of the LRP5 gene and BMD has been studied in several groups [18][19][20][21]. In these studies, BMD was measured at the lumbar spine, the femoral neck, and the trochanter, however, the total body BMD was not measured.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…We determined the A1330V (c.3989C>T) polymorphism of the LRP5 gene using the TaqMan (Applied Biosystems) polymerase chain reaction (PCR) method [20]. To determine the LRP5 SnP, we used an Assayson-Demand SnP Genotyping kit C__25752205_10 in embryonic development and oncogenesis [10,11].…”
Section: Determination Of a Snp In The Lrp5 Genementioning
confidence: 99%